Systellaspis debilis - Cardoso, Irene; Contents, Paulo Young Table Of (Zenodo, 2005)
Systellaspis debilis (A. Milne Edwards, 1881) (Figs 49–53) Acanthephyra debilis A. Milne Edwards, 1881: 13. Miersia gracilis Smith, 1882: 70. Systellaspis Bouvieri Coutiére, 1905: 8, fig. 3. Systellaspis debilis — Crosnier & Forest, 1973: 87, figs 26b, 27b; Chace, 1940: 181, fig. 51; 1986: 67, figs 34m –o, 35g, h. Material examined: Oceanprof I: A9, 22°41'S, 40°02'W, 1609m, 1 male (13.5mm), MNRJ 19222; A8, 22°48'S, 40°15', 1324m, 1 female (13mm), MNRJ 19221. Diagnosis: Carapace with rostrum overreaching scaphocerite, ventral margin with about ten teeth, dorsal margin with about 15 teeth; antennal spine absent; branchiostegal spine present, without distinct carina. Abdomen not dorsally carinate on all somites; somites 3 to 5 with posteromesial tooth, the one of somite 3 distinctly strong. Tergum of abdominal somites 4 and 5 with markedly spinulose margin. Male pleopod 1 with endopod rounded, bilobed at apex, numerous densely articulated plumose setae on lateral margins, several hook setae at apex; male pleopod 2 with appendix masculina, little longer than appendix interna, rounded on distal portion. Description: Eyestalk with ocellus on mediodistal portion (Fig. 49B). Carapace with rostrum usually longer than carapace, overreaching scaphocerite, ventral margin convex, with about ten teeth, dorsal margin with about 15 teeth (Fig. 49A); dorsal margin not carinate; antennal spine absent; branchiostegal spine present, without distinct carina; supraorbital and pterygostomian spine absent; cervical groove and suprabranchial carina absent; small hepatic carina present (Fig. 49A). Stylocerite broad at base narrowing at tip, acute apex reaching 3/4 of first antennular peduncle article (Fig. 49C). Scaphocerite with blunt apex, strong distal tooth overreaching blade, densely plumose setae on inner margin (Fig. 49D). Mandible with palp threearticulated, incisor process with about 13 strong, serrate teeth and about five small teeth; molar process formed by three rounded teeth in left mandible and by concavity where the teeth fits in right mandible (Fig. 50A, B). Maxilla 1 with two endites; distal endite with numerous stout, pectinate setae on inner margin; basal endite with pectinate setae on all margins; palp elongate, rounded apex, stout seta and spinose protuberance on inner margin (Fig. 50C). Maxilla 2 with two endites; distal endite bilobed, both lobes with pappose setae on inner margin; basal endite bilobed, distal lobe with scattered plumose and pappose setae on inner margin, basal lobe rounded, unarmed; endopod 2/3 endites length, several pappose setae on apex; scaphognathite with densely plumose setae on all margins (Fig. 50D). Maxilliped 1 with two endites; both endites with pappose setae on inner margin; endopod threearticulated, longer than distal endite, several plumose setae on apex, pappose setae on inner margin; exopodal lobe with densely plumose setae on all margins (Fig. 50E). Maxilliped 2 endopod with ischium and merus elongate pappose setae on inner margin; carpus short; propod rounded, long, stout, pectinate setae on inner margin; dactyl with long, stout, pectinate setae on inner margin; elongate exopod, densely plumose setae on all margins (Fig. 50F). Maxilliped 3 slender and elongate, with densely plumose setae in all articles; ischiummerus with distal stout seta on outer margin; propoddactyl with tufts of stout setae on inner margin; exopod with densely plumose setae on all margins (Fig. 50G). Pereopods 1 and 2 chelate. Pereopod 3 ischium with six stout setae and merus with 16 stout setae on inner margin. Pereopod 4 ischium with four stout setae and merus with nine stout setae on inner margin, and four stout setae on outer margin. Pereopod five ischium with one stout seta and merus with four stout setae on inner margin and one stout seta on outer margin (Fig. 49A). Epipods with mesial teeth on pereopods 1 to 3; epipod of pereopod 4 well developed, except for vertical component (Fig. 51A, B). Abdomen not dorsally carinate on all somites; somites 3 to 5 with posteromesial tooth; the one of somite 3 distinctly strong, the one of the somite 4 slightly projected upwards; somite 6 longer than somite 5. Tergum of abdominal somites 4 and 5 with markedly spinulose margins (Fig. 49A). Male pleopod 1 endopod distally bilobed; articulated, plumose setae on posterior margin, several pappose setae on basal anterior margin, stout setae on distal anterior margin, hook setae on anterior distal lobe (Fig. 51C). Male pleopod 2 with appendix masculina elongate, articulated, plumose setae on anterior margin, pectinate setae on apex; appendix interna about 2/3 length of appendix masculina, densely plumose setae on lateral margin, apex with a slightly triangular shape and many hook setae (Fig. 51D). Female pleopod 1 endopod leafshape, numerous articulated, plumose setae on posterior margin and pappose setae on anterior margin (Fig. 51E). Exopod of uropod with complete diaresis, one distal spine on outer margin (Fig. 52). Telson sulcate in dorsal midline; with six pairs of stout setae, spinose end piece formed by four pairs of stout setae, flanked by one pair of long stout setae (Fig. 52). Distribution: Western Atlantic: south of Greenland, Bermuda, Gulf of Mexico, Bahamas, Caribbean Sea, Brazil (Rio de Janeiro). Eastern Atlantic: Azores; west African coast, Nigeria, Congo, Angola. Indian and Pacific: Madagascar, Philippines, Indonesia, Hawaii. Adults probably live in depths between 300 and 600 m (Coutiére 1905; Chace 1940, 1986). Remarks: Systellaspis debilis occurs in the Indian, Pacific and Atlantic Oceans. In the Western Atlantic, this species was previously recorded from North and Central America. This is the first record of this species from South American waters (Fig. 53). The genus Systellaspis comprises five species, four of them occur in Western Atlantic. Two of the Western Atlantic species have a carapace with gastroorbital carina, extending from orbit to posterior margin, distinct from Systellaspis pellucida (Filhol, 1885) and S. debilis which have the carapace without gastroorbital carina extending from orbit to posterior margin. Systellaspis pellucida has the rostrum with 11 dorsal and five ventral teeth, the tergum of abdominal somites 4 and 5 is not spinulose, and the dorsal tooth on abdominal somite 4 is not directed upwards, whereas S. debilis has the rostrum with 15 dorsal and ten ventral teeth, the tergum of abdominal somites 4 and 5 is spinulose and the dorsal tooth on abdominal somite 4 is slightly directed upwards. The material examined agrees with Chace's (1986) description in the tergum of abdominal somites 4 and 5 with spinulose margin, in the dorsal tooth of abdominal somite 4 slightly directed upwards, and in the telson with 4–8 pairs of dorsolateral stout setae. The material examined also agrees with the figures of Crosnier & Forest (1973) in the these characters and in the rostrum with 3 to 4 prerostral teeth projected upwards. However, in the present material, the antennal spine is absent. : Published as part of Cardoso, Irene & Contents, Paulo Young Table Of, 2005, Deep-sea Oplophoridae (Crustacea Caridea) from the southwestern Brazil, pp. 1-76 in Zootaxa 1031 (1) on pages 64-69, DOI: 10.11646/zootaxa.1031.1.1, http://zenodo.org/record/5050357 : {"references": ["Smith, S. I. (1882) Reports on the results of dredging, under the supervision of Alexander Agassiz, on the east coast of the United States, during the summer of 1880, by the U. S. coast survey steamer \" Blake \", commander J. R. Bartlett, U. S. N., commanding: Report on the Crustacea, Part I. Decapoda. Bulletin of the Museum of Comparative Zoology at Harvard College, 10 (1), 1 - 108.", "Coutiere, H. (1905) Note preliminaire sur les eucyphotes recueillis par S. A. S. le prince de Monaco a l'aide du filet a grande ouverture (campagnes de la \" Princesse Alice \" 1903 - 1904). Bulletin du Musee Oceanographique de Monaco, 48, 1 - 35.", "Crosnier, A. & Forest, J. (1973) Les crevettes profondes de l'Atlantique oriental tropical. Faune Tropicale, 19, 1 - 409.", "Chace, F. A. (1940) Plankton of the Bermuda Oceanographic expeditions, IX: The Bathypelagic Caridean Crustacea. Zoologica, 25 (2), 117 - 209.", "Chace, F. A. (1986) The Caridean shrimps (Crustacea: Decapoda) of the Albatross Philippine Expedition, 1907 - 1910, part 4: families Oplophoridae and Nematocarcinidae. Smithsonian Contributions to Zoology, 432, 1 - 82."]}